1995
DOI: 10.1007/bf02348662
|View full text |Cite
|
Sign up to set email alerts
|

Significance of superoxide dismutase (SOD) in human colorectal cancer tissue: Correlation with malignant intensity

Abstract: The significance of superoxide dismutase (SOD) activity in colorectal cancer tissue was determined from the aspect of the antioxidant defense system. SOD activity and thiobarbituric acid reactive substance were measured in the tumor, in tissues adjacent to the tumor, and in regions that appeared normal, and the results were analyzed in terms of various histopathological factors (stage of disease, depth of invasion, venous invasion, etc.). DNA ploidy pattern and cell proliferation in cancer tissue were also mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 17 publications
5
30
1
Order By: Relevance
“…Ofner et al (1994) Furthermore. an increased SOD activity level of carcinomas was found to be associated with the malignant intensity of colorectal carcinomas (Satomi et al 1995). In our present study, however.…”
Section: Discussioncontrasting
confidence: 64%
“…Ofner et al (1994) Furthermore. an increased SOD activity level of carcinomas was found to be associated with the malignant intensity of colorectal carcinomas (Satomi et al 1995). In our present study, however.…”
Section: Discussioncontrasting
confidence: 64%
“…It has been hypothesized that deficiencies in nutritional antioxidants may exacerbate damage associated with the increased production of H 2 O 2 resulting from the enhanced activity of Sod2. A variety of epidemiologic studies have also linked increases in Sod2 levels, independent of polymorphism, with significant increases in colon, gastric, lung, and breast cancers, as well as mesothelioma and glioblastoma (7,39,(47)(48)(49)(50)(51). Of these studies, the increases in Sod2 activity or mRNA from tumor to normal tissue vary.…”
Section: Discussionmentioning
confidence: 99%
“…Both SOD and glutathione are antioxidants capable of scavenging free radicals or reactive oxidative species (ROS). Some reports have suggested that the accumulation of oxygen radicals in malignancies is actually accompanied by a reduction in SOD activity (50,51). In mouse myeloma cells, ˆ-3 fatty acids enhanced formation of superoxide anion, hydrogen peroxide and lipid peroxides but also caused reduced levels of antioxidant enzymes such as SOD, glutathione peroxidase (52).…”
Section: Discussionmentioning
confidence: 99%